The influence of peer friendships on drinking patterns among students at the University of Limpopo (Turfloop Campus) - Neluvhalani, Mpho Daphney (My University, 2015)
The present research investigated the relationship between peer friendships and alcohol drinking patterns, amongst second year students at the University of Limpopo (Turfloop campus). The use and abuse of alcohol amongst students in South African and globally is problematic and increases decade after decade. Students consider alcohol consumption a normal part of university life and often overlook the consequences of health and social problems associated with high levels of alcohol use. The study utilised a quantitative approach with a cross sectional survey design. A convenience sample of second year students was used. Descriptive statistics were used to present the results as they give a clear and concise picture of the data. The chi-square test was utilised to see if there were any significant differences between male and female participants in terms of the study propositions and questions. The results suggest that positive psychosocial and psychological needs are intrinsic and are more likely to occur if an individual has ongoing and positive peer friendships, particularly amongst female participants. Generally, significant results indicate that females are more likely to engage in positive peer friendships and behaviours than males. Responses from male participants suggest that they are more likely to engage in maladaptive behaviours and are more likely to be negatively influenced by their peers, in terms of alcohol consumption, than females. However, females may tend to underestimate how much they drink as they are less likely to go out to a bar and are more likely to drink in their rooms or homes with friends than males.
Thesis (MA. (Clinical Psychology)) -- University of Limpopo, 2015.
Keywords: Peer friendships; Alcohol drinking patterns; Peer pressure; Students -- Alcohol use -- South Africa -- Limpopo; Education, Higher -- Social aspects -- South Africa -- Limpopo